2005
DOI: 10.1359/jbmr.041224
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting Data to Body Size: A Comparison of Methods as Applied to Quantitative Trait Loci Analysis of Musculoskeletal Phenotypes

Abstract: The aim of this study was to compare three methods of adjusting skeletal data for body size and examine their use in QTL analyses. It was found that dividing skeletal phenotypes by body mass index induced erroneous QTL results. The preferred method of body size adjustment was multiple regression.Introduction: Many skeletal studies have reported strong correlations between phenotypes for muscle, bone, and body size, and these correlations add to the difficulty in identifying genetic influence on skeletal traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 25 publications
(26 reference statements)
1
51
0
2
Order By: Relevance
“…The association of chromosomal segments linked to both cortical bone parameters and weight (Table 2) is consistent with previous studies (Table 3) [24,30,33,51]. Body weight is one of the biggest intrinsic factors of bone strain [50], which is directly related to cortical area [33]. Based on these data, we postulate that the correlation between body weight and femur bone traits across strains may be at least partially due to skeletal loading.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The association of chromosomal segments linked to both cortical bone parameters and weight (Table 2) is consistent with previous studies (Table 3) [24,30,33,51]. Body weight is one of the biggest intrinsic factors of bone strain [50], which is directly related to cortical area [33]. Based on these data, we postulate that the correlation between body weight and femur bone traits across strains may be at least partially due to skeletal loading.…”
Section: Discussionsupporting
confidence: 89%
“…There is considerable evidence that skeletal traits positively correlate with body size phenotypes [32,50,51]. We found a positive correlation between body weight and the midfemur cortical bone area (r 2 = 0.63) and distal femur trabecular BV/TV (r 2 = 0.45), but there was no correlation between body weight and trabecular BV/TV in the lumbar vertebra (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Total radioactivity in the whole tissues of brain, liver, intestine, kidney, heart, lung, and muscle, as well as plasma was measured. Total muscle weight was calculated according to the muscle/body weight index of mice (19). Total plasma volume was estimated as 2 ml in a 20-g mouse (20).…”
Section: Methodsmentioning
confidence: 99%
“…FAT was highly correlated with 9WK in females but not in males (Figure 1), illustrating the sex-dependent relationship between these two traits. Several recent studies have suggested that due to the lack of equality in this relationship between the sexes (Stylianou et al 2006) and because of induced spurious correlation between the traits (Lang et al 2005), the use of ratios like adiposity index (fat pad mass/body weight 3 100) in QTL analysis may result in statistical artifacts. Therefore, to circumvent potential problems, we chose to adjust FAT (in the HG2DF 2 cross) and gonadal fat pad weight (GFP) (in the HG11F 2 cross) by including weight at sacrifice (WSAC) and WSAC 3 sex terms as additive covariates in both Model_A and Model_SI.…”
Section: Micementioning
confidence: 99%